Intermittent Exposure to Hypobaric Hypoxia Increases VEGF, HIF-1α, and Nrf-2 Expressions in Brain Tissue - Wardaya Wardaya; Dewi Sukmawati; Nurhadi Ibrahim; Frans Ferdinal; Ninik Mudjihartini; Mohamad Sadikin; Sri Widia A. Jusman; Irawan Satriotomo; Wawan Mulyawan (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Hypoxia inducible factor-1α (HIF-1α), nuclear factor erythroid 2-related factor 2 (Nrf-2), and vascular endothelial growth factor (VEGF), play a crucial role as neuroprotective factors. Currently, there is a lack of studies examining the biomolecular responses of the brain to intermittent hypoxia resulting from various pressures. This study was conducted to investigate the physiological responses, histopathological features, and cellular adaptive responses in the brains of rats that were intermittently exposed to hypobaric hypoxic conditions.METHODS: Thirty male Sprague Dawley rats were divided into six groups: a control group and five treatment groups exposed to hypobaric hypoxia. The treatment groups were placed in a hypobaric chamber simulating an altitude of 3,048 meters for 1 hour/day for 1, 7, 14, 21, and 28 days. After exposure, brain tissue was collected for histopathological analysis and protein quantification of HIF-1α, Nrf-2, cytoglobin (Cygb), neuroglobin (Ngb), VEGF, malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase (CAT).RESULTS: In the brain, intermittent hypobaric hypoxia significantly increased HIF-1α expression (p=0.000) and its downstream proteins Cygb (p=0.000), and VEGF (p=0.001), with a peak at 14x IHH exposure compared to control. This was followed by a significant increase in Nrf-2 expression (p=0.000), SOD (p=0.000), Gpx (p=0.000), and CAT activity (p=0.000), indicating an adaptive antioxidant response. Conversely, MDA levels was decreased with prolonged exposure, suggesting reduced oxidative damage.CONCLUSION: IHH elevates HIF-1α, Nrf-2, and oxidative stress markers, triggering an adaptive antioxidant response in the rat’s brains.KEYWORDS: HIF-1α, intermittent hypobaric hypoxia, Nrf-2, oxidative stress